2019
DOI: 10.1016/j.gr.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling weathering episodes in Tertiary regoliths by kaolinite dating (Western Ghats, India)

Abstract: Secondary minerals in soils can record climatic changes affecting continental surfaces over geological times. Their dating should refine our present knowledge about their potential periods of formation as well as their relations with the ongoing change of climate and erosion/weathering regimes. In the present study, twenty kaolinite samples from two lateritic profiles of the Karnataka plateau, an intensively studied area in the southern India, have been dated using electron paramagnetic resonance (EPR) spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…All the modern rivers flow on the antecedent valley and show five stages of terraces–evolutionary history, the relics of which could be recognized in the field (Figures ) as well as DEM (Figure ). While the inheritance of first stage could be envisaged from the occurrence of 53‐ to 50‐Ma old Mn‐rich laterite, the remaining four different stages (1, 3.5, 9, and 39 Ma that fall within a range of 0.229 ± 0.24 Ma to 40.73 ± 1.537 Ma) of kaolinitic contents in lateritic profiles of the study area reported by Mathian et al () also correspond to the developmental stages of landscapes as enumerated in the model (Figure a,b). Active continuance of landscape evolution as a result of tectono–climatic factors could be gauged from the occurrences of organic‐rich layer within flood deposits as young as 1,250–830 years BP ± 30.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…All the modern rivers flow on the antecedent valley and show five stages of terraces–evolutionary history, the relics of which could be recognized in the field (Figures ) as well as DEM (Figure ). While the inheritance of first stage could be envisaged from the occurrence of 53‐ to 50‐Ma old Mn‐rich laterite, the remaining four different stages (1, 3.5, 9, and 39 Ma that fall within a range of 0.229 ± 0.24 Ma to 40.73 ± 1.537 Ma) of kaolinitic contents in lateritic profiles of the study area reported by Mathian et al () also correspond to the developmental stages of landscapes as enumerated in the model (Figure a,b). Active continuance of landscape evolution as a result of tectono–climatic factors could be gauged from the occurrences of organic‐rich layer within flood deposits as young as 1,250–830 years BP ± 30.…”
Section: Discussionmentioning
confidence: 55%
“…Depending on the parent rocks, these regions are represented by bauxite, laterite, calcrete, and ferruginous‐lateritic regolith. Recent studies have documented significant weathering episodes during 53–50 Ma in laterites of Dharwar Plateau during Palaeocene–Eocene thermal maximum and 37–23 Ma in the highlands during late Oligocene warming and during 2.5 Ma (Bonnet et al, , ) besides four stages of kaolinite formation in Western Ghats, namely, 1, 3.5, 9, and 39 Ma ± 0.24–1.537 ago (Mathian et al ), indicative of the occurrences of inherited regoliths as well as active periods of weathering since the formation of modern/younger drainage basins (i.e., precollision and postcollision).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations